Financial and Social Performance of Indonesia's State-Owned Islamic Banks - Utari Evy Cahyani; Rizal Ma'ruf Amidy Siregar (UIN Raden Mas Said Surakarta, 2021)
The government has started the process of merging three state-owned bank's sharia subsidiaries to accelerate the growth of Islamic banking in Indonesia. This study was conducted to see the effect of financial performance as measured by Return on Assets (ROA) and Firm Size on social performance as measured by Islamic Social Reporting (ISR) index. This study uses data that form of annual reports published by Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah (BNIS) and Bank Rakyat Indonesia Syariah (BRIS) in 2010-2019. Islamic Social Reporting (ISR) is the dependent variable with Return on Assets (ROA) and Firm Size as independent variable. Fixed effect model is better than random effect model in this research. ROA have no effect on ISR. Whereas Firm Size have positive effect on ISR. It means thath the larger banking size the better the social performance. The new state-owned Islamic bank with the bigger size also improve social performance.